Pengaruh Metode Mind Mapping dalam Model Pembelajaran POGIL Terhadap Hasil Belajar Peserta Didik Kelas XI MIA MA DDI Cambalagi (Studi pada Materi Pokok Larutan Penyangga) - Amalia, Risna; Side, Sumiati; Muhharram, Muhharram (ChemEdu, 2025)
This research is a quasi-experimental research that aims to determine the effect of using themethod mind mapping in the learning model POGIL on the learning outcomes of students in class XI MIA MA DDI Cambalagi Maros on the subject matter of buffer solution. This research was carried out in the even semester of the 2020/2021 academic year in March in class XI MIA MA DDI Cambalagi Maros. Maros Regency, South Sulawesi Province. The population in this study were students of class XI MIA MA DDI Cambalagi Maros which consisted of six classes. The sampling technique was carried out using a simple random sampling technique. Class XI MIA 1 as the experimental class and class XI MIA 2 as the control class, each of which is 28 people. Data was collected by giving posttest to the experimental class and the control class. This study uses descriptive and inferential statistical analysis. The results of statistical analysis showed that the average learning outcomes of the experimental class were 74.24, which was higher than the control class, which was 45.8. The results of inferential statistical analysis on student learning outcomes showed that the experimental class and control class data came from a homogeneous population but not normally distributed so that the hypothesis test used was thetest Mann-Whitney with = 0.05 obtained Zcount > Ztable (6 ,06 > 1.64). With this, it can be concluded that there is an effect of using themethod mind mapping in themodel process oriented guided inquiry learning on the learning outcomes of class XI MIA MA DDI Cambalagi Maros students on the buffer solution material. Keywords : mind mapping, pogil, learning outcomes, buffer solution